Structure–property relations of three-dimensional nanoporous template-based graphene foams. (July 2022) - Peng, Weixiang; Sun, Kun; Onck, Patrick
Abstract: Recently, much attention has been directed to 3D graphene structures due to their potential of retaining intrinsic 2D graphene properties, in combination with structural flexibility and tunable porosity. From a theoretical point of view, however, it is challenging to build 3D graphene foam structures that accurately represent experimental topological configurations. Here, we generate open-cell 3D graphene structures that closely reflect template-based manufacturing techniques and investigate their mechanical properties. We use all-atom molecular dynamics simulations to relate the overall stiffness, collapse stress and fracture properties to the underlying graphene microstructure represented by the graphene relative density, template relative density and number of graphene layers. We do so for four different template morphologies: gyroids, regular foam (BCC), random foam and nanoporous gold. The overall mechanical properties as a function of graphene relative density are analyzed in terms of power law relations to probe the microstructural deformation modes. Our results show that the open-cell 3D graphene structures feature bending as the dominant deformation mode, with regular graphene foams having the highest stiffness and strength and random foams the lowest. For gyroids we found that a higher template relative density leads to reduced mechanical properties but improved ductility. A similar trend was observed when the number of graphene layers was increased: enhanced ductility but at the expense of a reduced strength. Interestingly, we found that for low graphene density, the gyroids feature a strong self-stiffening response, leading to improvements in both strength as well as ductility. Our findings can be used as a guideline for the experimental design of innovate and lightweight graphene structures with strongly enhanced mechanical properties. Graphical abstract: